2009
DOI: 10.1016/j.jcin.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Plaque at Nonculprit Lesions in Patients Enrolled in Intravascular Ultrasound Atherosclerosis Progression Trials

Abstract: Attenuated plaque is present in a significant number of nonculprit segments in patients enrolled in IVUS progression trials and remains stable during follow-up. There is a relationship with mixed calcified lesions. These findings challenge the prior assumption that attenuated plaque is a finding limited to culprit lesions associated with acute clinical presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 28 publications
(26 reference statements)
0
20
1
Order By: Relevance
“…Three articles were further excluded due to no record of slow/no reflow phenomenon or clinical outcomes (13,15,21). Five observational studies, which described the association between attenuated plaques and incidence of slow/no reflow during PCI (11,14,16,22) and five studies that presented MACEs were included in the final meta analysis (Figure 2) (12,14,18,19,23).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three articles were further excluded due to no record of slow/no reflow phenomenon or clinical outcomes (13,15,21). Five observational studies, which described the association between attenuated plaques and incidence of slow/no reflow during PCI (11,14,16,22) and five studies that presented MACEs were included in the final meta analysis (Figure 2) (12,14,18,19,23).…”
Section: Search Resultsmentioning
confidence: 99%
“…Two studies involved ACS patients (13,14) and one study involved all CAD patients (11). Five other studies reported the MACEs (12,14,18,19,23). The sample size was 110 to 2,072 for these studies.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, noncalcified carotid plaques commonly exhibit a higher degree of fibrous cap inflammation, a key process in fibrous cap disruption. Calcification in ATS lesions is relatively common and has been implicated as a risk factor for increased cardiovascular morbidity and mortality (8,9), while Bayturan et al (10) and Hashimoto et al (11) demonstrated that carotid ATS plaque calcification is a structural marker for carotid plaque stability.…”
Section: Discussionmentioning
confidence: 99%